Large family genetic analysis: effects of variegated porphyria and hemophilia b on reproductive traits - Dorofieieva, Valeriia; Fedota, Olena (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2022)
Introduction. The relevance of the study of genetic pathologies is due to the growing prevalence in most countries, disability and mortality of persons, high costs of support and treatment. The modern classifications include various forms of porphyria and hemophilia. The study of pathologies in historical persons, when it is possible to collect information from different sources regarding members of a large family over a long period of time, is of interest for understanding the mechanisms of the development of the disease at the present time. Aim is to analyze the genetic characteristics of variegated porphyria and hemophilia B in a large family. Materials and methods. Data from current guidelines and clinical protocols, scientific literature and genetic databases (OMIM) on various forms of porphyria and hemophilia are analyzed. Information about 1362 people from the British royal family in 18–20th centuries was collected from open sources and scientific literature. A pedigree of 10 generations, 27 nuclear families with persons with variegated porphyria and hemophilia B has been compiled. Genealogical, segregation, linkage, statistical analysis was performed. The results were used to study reproductive traits. Results. Genealogical analysis showed a family accumulation of porphyria – its prevalence among relatives in a large family was 1,8 %, which is three orders of magnitude higher than among the population of different countries. It was established that there is no statistically significant difference in the sex ratio among patients with the specified pathologies. Data from genealogical and segregation analysis and a penetration rate of 92 % suggest an autosomal dominant type inheritance with incomplete penetrance of disease which is consistent with the literature. The independent nature of inheritance of variegated porphyria and hemophilia B was established. It was found that in persons with porphyria reproductive traits are 3,3–4,1 times differ than the reproductive traits of persons with porphyria and hemophilia at the same time. A statistically significant difference was established between the analyzed traits of patients with porphyria, who at the same time are carriers of the mutation that causes hemophilia, and the indicators of healthy individuals.